2004
DOI: 10.1111/j.1365-2982.2004.00591.x
|View full text |Cite
|
Sign up to set email alerts
|

Human mast cell mediator cocktail excites neurons in human and guinea‐pig enteric nervous system

Abstract: Neuroimmune interactions are an integral part of gut physiology and involved in the pathogenesis of inflammatory and functional bowel disorders. Mast cells and their mediators are important conveyors in the communication from the innate enteric immune system to the enteric nervous system (ENS). However, it is not known whether a mediator cocktail released from activated human mast cells affects neural activity in the ENS. We used the Multi-Site Optical Recording Technique to image single cell activity in guine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 28 publications
4
46
0
2
Order By: Relevance
“…Effects of intestinal bacteria on epithelial cells cannot be isolated from their effects on immune activation, neurotransmission and secretomotor responses, all of which will, in turn, impact on the initial stimulus. Previous work in animal models has demonstrated that changes in immune activation in the gut, have an impact in gut neuromotor activity [Barreau et al 2008;Verma-Gandhu et al 2007; Akiho et al 2007;Vallance et al 2007;Khan et al 2005;Schemann et al 2005;Sharkey and Mawe, 2002;Galeazzi et al 2001;Barbara et al 2001]. Work in germ-free (GF) animals has clearly demonstrated that in the absence of an intestinal microbiota, intestinal motility is disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of intestinal bacteria on epithelial cells cannot be isolated from their effects on immune activation, neurotransmission and secretomotor responses, all of which will, in turn, impact on the initial stimulus. Previous work in animal models has demonstrated that changes in immune activation in the gut, have an impact in gut neuromotor activity [Barreau et al 2008;Verma-Gandhu et al 2007; Akiho et al 2007;Vallance et al 2007;Khan et al 2005;Schemann et al 2005;Sharkey and Mawe, 2002;Galeazzi et al 2001;Barbara et al 2001]. Work in germ-free (GF) animals has clearly demonstrated that in the absence of an intestinal microbiota, intestinal motility is disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…46 Colonic mucosal mediators from IBS patients, which exert excitatory action on human submucosal neuron, 34 could also excite myenteric cholinergic motor neurons. 47 It correlated with MCs counts and mediated by activation of prostanoid receptors, TRPV1 and P2X receptors. 48 This supported the concept that MCs can impact on smooth muscle contractility or on intrinsic motor neurons.…”
Section: Mast Cells Regulate Gastrointestinal Motilitymentioning
confidence: 99%
“…Microiontophoretic application of compound 48/80, an activator of mast cells, in thalamus caused excitation and inhibition on thalamic neurons possibly through mast cell degranulation (122). Moreover, local application of a mast cell mediator cocktail that was released from isolated human intestinal mucosa mast cells stimulated by IgE receptor crosslinking onto individual ganglia evoked an excitatory response consisting of action potential discharge in neurons of guinea-pig and human submucous plexus, and guinea-pig myenteric plexus (123). Mediators of mucosal mast cells from inflammatory bowel disease patients also markedly enhanced the firing of mesenteric nerves (124).…”
Section: In Vivo Relevancementioning
confidence: 99%